THE IMPLEMENTATION OF HYBRID METHODS FOR NUMERICAL SIMULATION FLOW ANALYSIS AROUND AN AIRCRAFT WITH THE USE OF OpenFOAM SOFTWARE PACKAGE - A. S. Epikhin; V. T. Kalugin (Научный вестник МГТУ ГА, 2016)
The article describes the possibility of implementing the open source CFD software package OpenFOAM for aerodynamic characteristics calculation of aircraft taking into account the local turbulence flows. Computational simulation methods of turbulent flows were reviewed and it was recommended to use eddy-resolving approaches and to carry out the analysis of numerical schemes and constants of subgrid model for computational calculation of large scale vortex. The article contains recommendations how to use different turbulence models for numerical simulation of unsteady vortex flows. The analysis of numerical schemes was carried out by solving the problem of homogeneous isotopic turbulence decay on the bases of software package OpenFOAM and RANS-LES approach implementation. The method of combined implementation of RANS-LES approaches with the use of zonal RANS-LES methods were described and implemented in OpenFOAM software package. As an example of the hybrid RANS-LES approach the task of simulation flow field around an aircraft with airbrake at subsonic speed (50 m/s) has been tested. Flow structure has been obtained and compared with experimental data and other simulation methods.